Reflective teaching skills development through classroom action research: enhancing pre service teachers' reflection on action in practicum - Dalimawaty Kadir; Andi Asari; Sofia Annisa (JRTI (Jurnal Riset Tindakan Indonesia), 2026)
Reflective skills are essential competencies for pre-service teachers to drive continuous instructional improvement through critical evaluation. However, many candidates struggle to advance beyond basic descriptive processing. This study investigated the efficacy of a two cycle Classroom Action Research (CAR) intervention in systematically enhancing the reflective skills of 35 purposively sampled pre-service teachers during their teaching practicum. Data were gathered through a 10 item observation scale () and guided journals evaluated using a standardized rubric with strong inter-rater consensus (). Quantitative diagnostics revealed a significant rise in overall reflective competence from a baseline mean of  in Cycle I to  in Cycle II. A paired-samples t-test confirmed this growth (), supported by a moderate normalized gain () and an exceptionally large effect size (). Crucially, the intervention prompted a major behavioral shift across operationalized reflection levels: technical reporting (descriptive) plummeted from 68% to 18%, while diagnostic reasoning (analytical) grew to 52%, and holistic, theory to practice integration (critical) tripled from 10% to 30%. These findings demonstrate that CAR functions not merely as an inquiry design, but as a powerful pedagogical scaffolding strategy to cultivate higher order professional thinking in teacher education.